Respuesta :
Answer:
see below
Step-by-step explanation:
f(x) = -2/3 (x+1) (x-5)
First find the zeros
0 = -2/3 (x+1) (x-5)
Using the zero product property
x+1 =0 x-5=0
x= -1 x = 5
Then find the y intercept
y = -2/3 (0+1)(0-5)
- 2/3 (1)(-5)
+10/3
We know that this is a parabola that opens downward
![Ver imagen wegnerkolmp2741o](https://us-static.z-dn.net/files/d8b/a0b8df0c73da1bfaefe3d17dcc773b04.png)
Simplify
- y=-2/3(x+1)(x-5)
- y=-2/3(x(x-5)+x-5)
- y=-2/3(x²-5x+x-5)
- y=-2/3(x²-4x-5)
Graph attached
![Ver imagen MisterBrainly](https://us-static.z-dn.net/files/daa/b93ad5340011ba7d07a2888281f380be.jpg)